Structural, molecular, functional and immunological characterization of Wuchereria bancrofti-galectin - Yasin, Nazeer; Laxmanappa, Hoti Sugerappa; Muddapur, Uday M.; Cheruvathur, Jennifer; Prakash, S. M. Udaya; Thulasiram, Hirekodathakallu Venkataramaiah (International Journal of Biological Macromolecules, 2020)
Galectins regulate growth and differentiation of immune cells and inflammation through their carbohydrate-binding function in humans, while also play a role in parasite survival. This study focused on the galectin of lymphatic filarial parasite Wuchereria bancrofti (Wb-Gal). The multiple sequence alignment with other galectins showed that the Wb-Gal belonged to galactoside binding lectin family, particularly tandem repeat type galectin-9. A homology model of Wb-Gal was developed in the I-TASser server using high similarity 3D structures with a quality score of 89.5. Molecular docking and dynamics studies revealed that the CCRD and NCRD of Wb-Gal bind with galactose and lactose. Further, Wb-Gal was cloned into the pET28 vector, expressed in E. coli Rosetta strain and purified by affinity chromatography. In the hemagglutination assays, the rWb-Gal bound to lactose, galactose, and glucose. Indirect Enzyme-Linked Immunosorbent Assay (ELISA) using different clinical filarial sera showed that the IgG and IgM response was against Wb-Gal x very high in all filarial clinical groups, whereas the IgA and IgG2 response was minimum to negligible. There was an enhanced response of IgG1 and IgG4 antibodies in Microfilaremics (MF) cases compared to Chronic Pathology (CP) and Endemic Normal (EN) individuals. Interestingly, the IgE response was comparatively higher in EN than MF and CP. These studies show that Wb-Gal is a member of the lectin family of proteins binding to different carbohydrates and may have an important role in the pathophysiology of filarial infection which needs to be investigated in greater detail. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Filariasis; Hemagglutination assay; Immunomodulation; Wuchereria bancrofti galectin